Date (Phoenix dactylifera L.) seed oil is an agro-industrial waste with biopreservative effects and antimicrobial activity - Hana Alkhalidy; Anas A. Al-Nabulsi; Marah Al-Taher; Tareq Osaili; Amin N. Olaimat; Dongmin Liu (Scientific Reports, 2023)
Abstract Antimicrobial resistant (AMR) infections are a leading health threat globally. Previous literature has underscored the farm-to-fork continuum as a potential focal point for the emergence and spread of AMR. In the present study, date (Phoenix dactylifera L.) seed oil was investigated for its chemical composition and antimicrobial activity against common foodborne pathogens including Escherichia coli O157:H7, Salmonella enteritidis, Salmonella typhimurium, Listeria monocytogenes, and Staphylococcus aureus in vitro, and in ultra-high-temperature (UHT) milk as a food model at storage temperatures of 37 °C (24 h) and 10 °C (7 days). GC–MS analysis of the seed oil revealed 20 compounds, with octadecane (52.2–55.4%) as the major constituent, and the fatty acid analysis revealed 17 fatty acids, with oleic acid (42.3–43.1%) as the main constituent, followed by lauric acid (19.8–20.3%). The antimicrobial activity of date seed oil was determined using the microdilution method. A significant inhibition against gram-negative bacteria was noted in microbiological media and UHT milk, with a log reduction ranging from 4.3 to 6.7 (at 37 °C/24 h) and 5.7 to 7.2 (at 10 °C/7 days), respectively, at oil concentrations ranging between 10 and 15 µl/ml. The oil showed a similar significant inhibitory effect against St. aureus in the microbiological media (2.0–6.0 log reduction), whereas the inhibitory effect against L. monocytogenes was not statistically significant, with a maximum log reduction of 0.64 achieved at a concentration of 10 µl/ml. AFM imaging of the bacteria showed that oil treatment led to morphological changes in the bacteria including the formation of distorted shapes, surface blebs, indentations, stiffness, and swelling. Present findings suggest that date seed oil can be a promising by-product with potential antimicrobial activity and a food preservative.